(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As the world is going through the phase of transformation from the conventional services delivery system to the Information and Communication Technology based services delivery system which ensure the efficiency and effectiveness of the services with low cost. In this context, an attempt has been made in this paper to build up the concept of E-Health in general which is a part of this new way of services delivery system to the public. It is a study based on available literature to find out the challenges in implementing the Information and Communication Technology based health care services in India.